Applied Statistical Analysis: Regression Analysis of Islamic Banking Asset Growth and Conventional Banking Growth 2021-2022 - Risdayani, R; Isman, I; Hidayat, Syamsul; Nirwana, Andri (Universitas Muhammadiyah Surakarta, 2023)
This study aims to investigate and analyse the relationship between Islamic banking assets and conventional banking assets in Indonesia. The research methodology involves the use of a linear regression test to determine the dependence relationship between Islamic banking assets (dependent) and conventional banking assets (independent). The results of the analysis showed that there was a significant negative relationship between the variables and the dependent variable, with a significance value of 0.441 (> 0.05). The regression equation obtained Y=0.105-0.158X illustrates that if the independent variable (Islamic banking assets) increases, the dependent variable (conventional banking assets) will decrease, and vice versa. This research is expected to provide practical insights for practitioners to help stakeholders make more informational and informed decisions to make more informational and strategic decisions to achieve their goals.